The Influence of the Cost of Services on the Selling Price of Air Export Services Destination to Incheon City, Kr (ICN) at PT. NCS Line World Wide - Octaviani, Evania; Amelia, Rita (Institut Bisnis dan Informatika Kesatuan, 2023)
A company is a business entity that strives to always optimize the profits that can be generated from its operational activities. Optimizing profits requires adequate cost information to be used as a basis for determining planning and decision making. One of the important cost information for companies to pay attention to is information regarding the cost price. Cost price is an important factor in determining the selling price of a product, with the hope that if the product is sold the company will make a profit. This research aims to determine the effect of calculating the cost of services on determining selling prices in an effort to increase profits at PT NCS Line World Wide. The subject of this research is air export service activities to Incheon City. The results of this research reveal that the cost of services has a significant positive effect on selling prices. Keywords: selling price, cost price, profit